Normal Families of Holomorphic Functions Concerning Zero Numbers (Communications in Mathematical Research, 2019)
In this paper, we study the normal families related with a Hayman conjecture of higher derivative concerning zero numbers, and get one normal criterion.Our results improve some earlier related results.